Revisiting e-learning challenges in the Post-pandemic period: From rhetoric to reality - Souleles, Nicos (My University, 2024)
In 2005, six years after the term 'e-learning' was devised, I authored a paper titled "Staff use of e-learning and graduate competencies for the knowledge economy: A study of the misalignment between rhetoric and practice" (2005). Incidentally, 'e-learning' became 'elearning' without the hyphen in the early 2000s as online learning became widespread. This paper examined the dominant rhetoric of this initial period of elearning adoption by higher education (HE) institutions and the professional development of academics. At the time, the rhetoric was alarmist...
Keywords: Knowledge economy; eLearning; Professional development; Higher education